2020
DOI: 10.3389/fpubh.2020.00087
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Effect of a 50-Hz Electromagnetic Field at 500 μT on Parameters Related With the Cardiovascular System in Rats

Abstract: Background: Whether electromagnetic field (EMF) exposure affects the function of the cardiovascular system is under debate. The present study aimed to investigate the effects of 500 µT EMF exposure on the cardiovascular system in rats. Methods: Forty-eight-week-old male Sprague-Dawley rats were randomly divided into two groups: the sham group and the exposure group. During 24-week EMF exposure (20 h per day), the blood pressure and pulse rate were recorded every 4 weeks. Before sacrifice, electrocardiography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…long-term exposure to EMFs [19,20]. However, another two studies reported that there was no influence on the cardiovascular system among rats subjected to chronic exposure to an EMF [21,22]. The heart is a highly coordinated organ with the notable ability to adapt in response to physiological or pathological stresses in order to maintain homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…long-term exposure to EMFs [19,20]. However, another two studies reported that there was no influence on the cardiovascular system among rats subjected to chronic exposure to an EMF [21,22]. The heart is a highly coordinated organ with the notable ability to adapt in response to physiological or pathological stresses in order to maintain homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the mechanisms, Wei et al (2015) exerted a 2 mT, 15 Hz, 50 Hz, 75 Hz, and 100 Hz EMF on cardiomyocytes isolated from neonatal SD rats and confirmed the modulation of calcium-related activities, including the increase in calcium concentration baseline level and the decrease in the amplitude of calcium transients in the sarcoplasmic reticulum. However, long-term experiments of 24 weeks on rats indicated that 50 Hz EMF had no obvious effects on the cardiovascular system through the detection of blood pressure, pulse rate, heart rate, and cardiac rhythm (Zhou et al, 2016) or based on the results of echocardiography, cardiac catheterization detection, HE staining of cardiomyocytes, and mRNA levels of related genes (Liu et al, 2018;Zhang et al, 2020).…”
Section: Cardiovascular Systemmentioning
confidence: 99%